DEVELOPING COMMUNICATION SKILLS THROUGH LISTENING AND SPEAKING MATERIALS IN ENGLISH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The item under discussion shows how speaking and listening abilities are integrated to improve students' communication competence in Uzbek secondary schools and lyceums. The authors of the paper believe that since speaking and listening are always integrated in real life, educators should approach teaching these two abilities in a collaborative manner. Because these skills are not employed in integration, kids who are proficient in speaking and listening may still be unable to communicate in the language. Since this occurs in real life, using actual materials and scenarios could logically result in the integration of abilities.